Metal-free carbon monoxide-releasing micelles undergo tandem photochemical reactions for cutaneous wound healing - Cheng, Jian; Zheng, Bin; Cheng, Sheng; Zhang, Guoying; Hu, Jinming (Chemical science (Cambridge), 2020)
Carbon monoxide (CO) has shown broad biomedical applications. The site-specific delivery and controlled release of CO is of crucial importance to achieve maximum therapeutic benefits. The development of carbon monoxide (CO)-releasing polymers (CORPs) can increase the stability, optimize pharmacokinetic behavior, and reduce the side effects of small molecule precursors. However, almost all established CORPs were synthesized through a post functional approach, although the direct polymerization strategy is more powerful in controlling the chain compositions and architectures. Herein, a direct polymerization strategy is proposed toward metal-free CO-releasing polymers (CORPs) based on photoresponsive 3-hydroxyflavone (3-HF) derivatives. Such CO-releasing amphiphiles self-assemble into micelles, having excellent water-dispersity. Intriguingly, photo-triggered tandem photochemical reactions confer successive fluorescence transitions from blue-to-red-to-colorless, enabling self-reporting CO release in vitro and in vivo as a result of the incorporation of 3-HF derivatives. More importantly, the localized CO delivery of CORPs by taking advantage of the spatiotemporal control of light stimulus outperformed conventional metal carbonyls such as CORMs in terms of anti-inflammation and cutaneous wound healing. This work opens a novel avenue toward metal-free CORPs for potential biomedical applications. Metal-free carbon monoxide-releasing polymers (CORPs) are synthesized via a direct polymerization approach, exhibiting not only improved stability but also accelerated wound healing performance as compared to CORM-3.